Disparities between US Hispanic and non-Hispanic women in obesity-related perinatal outcomes: a prospective cohort study. (12th December 2022) - Stafford, Irene A.; Turrentine, Mark A.; Ostovar-Kermani, Tiffany; Moustafa, Ahmed S. Z.; Berra, Alexandra; Sangi-Haghpeykar, Haleh
Abstract: Background: Mortality figures and national health surveillance data have demonstrated that Hispanics have a 24% lower risk of all-cause mortality compared to their non-Hispanic counterparts despite increased rates of obesity and related illnesses. Objective: The aim of this study is to evaluate if this paradox exists for obesity-related perinatal outcomes in otherwise low-risk Hispanic women. Materials and methods: A prospective cohort study of low-risk women across all BMI classes with a singleton, non-anomalous term pregnancy admitted in active labor or undergoing induction of labor between May 2014 and April 2017. All demographic, obstetric, and neonatal outcomes were recorded, and the body mass index (BMI) closest to delivery was used for analysis. Data including composites of adverse maternal and neonatal outcomes were compared across BMI classes and between individuals of Hispanic and non-Hispanic ethnicity. Women with antenatal complications, prior cesarean delivery, and cesarean for non-reassuring fetal status were excluded. Results: Of the 11, 369 women who met inclusion criteria, 6303 (55%) were Hispanic. Eight percent of Hispanic women were normal weight (BMI: 18.5–24.9), 34% were overweight (BMI: 25–29.9), and 58% were obese (BMI > 30). Fourteen percent of non-Hispanic women were normal weight, 42% were overweight, and 44% were obese. The majority (65%) of women were multiparous. Rate of induction and birthweight increased across BMI for Hispanic and non-Hispanic groups, however the route of delivery was not significantly different ( p  = .22, 0.16, respectively). Although the association between BMI and composite perinatal complications did not differ by BMI class and ethnicity, the newborns of non-Hispanic women were more likely to be admitted to the neonatal intensive care unit with increasing maternal weight class (<0.001), even after adjusting for age, parity, marital status, prenatal visits, current tobacco use, type of labor, mode of delivery, and birthweight. Conclusion: There were no demonstrable differences in composite adverse maternal or neonatal outcomes between Hispanic and non-Hispanic obese women. However, newborns of non-Hispanic obese women were more likely to be transferred to the neonatal intensive care unit with increasing maternal BMI.